Silver Nanoparticles – Universal Multifunctional Nanoparticles for Bio Sensing, Imaging for Diagnostics and Targeted Drug Delivery for Therapeutic Applications - Sironmani, Anitha; Daniel, Kiruba (IntechOpen, 2011)
None